EFEKTIVITAS TERAPI SEFT (SPIRITUAL EMOTIONAL FREEDOM TECHNIQUE) DAN BERDZIKIR TERHADAP PENURUNAN TINGKAT KECEMASAN MAHASISWA PRODI D3 KEPERAWATAN DALAM MENGHADAPI OSCA : EFFECTIVENESS OF SEFT THERAPY (SPIRITUAL EMOTIONAL FREEDOM TECHNIQUE) AND Dhikr AGAINST LEVEL DECLINE ANXIETY OF D3 INTERNAL NURSING PROGRAM STUDENTS FACING OSCA - siswanto; Aseta, Pandu; Indriani, Frida (Politeknik Insan Husada Surakarta, 2024)
Students are very easy to experiencing anxiety problems, both physical and psychological. One of which is anxiety about facing exams. Students need coping to overcome their anxiety so that it doesn’t drag on, namerly SEFT therapy (Spiritual Emotional Freedom Technique) and pray dzikir. To determine the effect of SEFT (Spiritual Emotional Freedom Technique) therapy on reducing anxiety levels in D3 Nursing Study Program Student in facing OSCA. The method used in this research is quantitative research with a Quasy Experiment design using a one group prepostest design approach. Sampling in this study used purposive sampling of 35 respondents. The results of research from a sample of 35 respondents showed that 7 respondents (20%) were male and 28 respondents (80%) were female. There were 35 respondents (100%) of Muslim students and 0 respondents (0%) of non-Muslim students. The level of student anxiety before SEFT (Spiritual Emotional Freedom Technique) therapy was obtained: 21 (60%) respondents experienced mild anxiety, 12 (34,3%) respondents experienced moderate anxiety, and 2 (5.7%) respondents experienced anxiety. severe. The level of student anxiety after SEFT (Spiritual Emotional Freedom Technique) therapy showed that 14 (40%) respondents not anxious, 14 (40 % ) respondent mild anxiety, 7 (20%) moderate anxiety and 0 (0%) respondents severe anxiety Conclusion : There were changes and a decrease in anxiety levels in students after being given SEFT Therapy (Spiritual Emotional Freedom Technique)